Effect of Nebivolol, a Novel β1-Selective Adrenoceptor Antagonist with Vasodilating Properties, on Kidney Function - Greven, Joachim; Gabriëls, Gert (Arzneimittelforschung, 2000)
Nebivolol (CAS 99200-09-6) is a novel β1-selective adrenoceptor antagonist which possesses vasodilating properties and lowers systemic vascular resistance in dogs and humans, presumably by a nitric oxide-related mechanism. In the present study, clearance techniques were applied to anaesthetized male Sprague Dawley rats, and the effects of nebivolol on renal hemodynamics (glomerular filtration rate and renal plasma flow), on urinary excretion of sodium, chloride and potassium, on renal NO-excretion, and on plasma renin activity were studied. Nebivolol doses ranging from 0.1 to 2 mg/kg i.v. were tested. The results revealed that nebivolol dose-dependently increased glomerular filtration rate, urine flow and urinary excretion of sodium and chloride. Potassium excretion was only inconsistently increased and showed no dose dependency. At a dose of 1 mg/kg, the drug also significantly increased renal plasma flow measured as 3H-PAH (p-aminohippurate) clearance. The effect of nebivolol on the glomerular filtration rate could be abolished by L-NMMA (N6-monomethyl-L-arginine) (1 mg/kg), a non-selective inhibitor of NO-synthase and by iminoethyllysine (1 mg/kg), a relatively selective inhibitor of the inducible NO-synthase, but not by 7-nitroindazole (1 mg/ kg), a relatively selective inhibitor of the neuronal NO-synthase isoform. The saluretic effect of nebivolol was diminished by all of the three NO-synthase inhibitors, but could not be completely reversed. At a dose of 2 mg/kg, nebivolol increased renal NO-excretion by 70.7 %. This effect could be completely abolished by L-NMMA (1 mg/kg). Plasma renin activity was lowered by nebivolol (2 mg/kg) from 14.6 ± 1.49 to 6.5 ± 1.66 ng angiotensin I/ml/h (p < 0.01). The results demonstrate that, in anaesthetized rats, nebivolol exerts significant renal vasodilating effects and increases urinary excretion of fluid and solutes. The actions of nebivolol on renal hemodynamics are assumed to be mediated by a stimulation of the NO-synthase, probably the inducible isoform. Since none of the NO-synthase inhibitors could completely abolish the saluretic effect of nebivolol, an additional mechanism, not related to NO, may be involved in the tubular action of this drug.
Keywords: CAS 99200-09-6; Nebivolol, effect on kidney function, rat, renal hemodynamics, urinary excretion